TEACHER PERCEPTION IN COMPUTER ASSISTED INSTRUCTION, ADOPTION FOR EDUCATION SUPPORT IN PUBLIC SECONDARY SCHOOLS IN KENYA - Molenje, Mary; Mukwa, Prof. Chris; Too, Prof. J. (IJRDO- Journal of Educational Research, 2017)
Computers can provide a more flexible and effective ways of professional development for teachers to improve pre- and in-service, teachers training and connect teachers to the global teachers community. The purpose of this study was to investigate the teacher perception in computer assisted instruction, adoption for education support, in Kenyan secondary schools. The study sought to address the following objectives; Find out the teachers’ attitude towards the computer use and to assess the perceived barriers towards computer instruction. The study adopted the technology acceptance model (TAM) by Davis (1989) which expresses how technology is integrated into the instruction process. Other theories include, Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB). A descriptive survey research design was used. Stratified sampling was used to select One hundred and fifty schools; Purposive sampling was used to select the Head teachers and Simple random sampling was used to select the teachers. A total representative sample of 414 respondents was used. Questionnaires and interviews schedules were used as instruments for data collection. Internal consistency (Reliability) of the research instrument was ascertained using the test re test technique as well as Cronbach’s alpha of 0.75 and above. Data was coded and analyzed using Statistical Package for Social Sciences (SPSS) Version 21.0 as well as STATA version 13.0.Descriptive statistics such as frequencies, percentages and means was used to analyze the data. Data was presented in tables and pie charts appropriately. The study would benefit teachers, school managers, curriculum planners and policy makers, developers and implementers in coming up with the best integration approaches for the use of computers in teaching and learning in Kenyan secondary schools.